The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1128/jvi.78.20.10960-10966.2004
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Proteins in Human Cytomegalovirus (HCMV) Particles: the HCMV Proteome

Abstract: Human cytomegalovirus (HCMV), a member of the herpesvirus family, is a large complex enveloped virus composed of both viral and cellular gene products. While the sequence of the HCMV genome has been known for over a decade, the full set of viral and cellular proteins that compose the HCMV virion are unknown. To approach this problem we have utilized gel-free two-dimensional capillary liquid chromatography-tandem mass spectrometry (MS/MS) and Fourier transform ion cyclotron resonance MS to identify and determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
355
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 526 publications
(376 citation statements)
references
References 42 publications
18
355
3
Order By: Relevance
“…This finding leans toward excluding the possibility that IFI16 nonspecifically aggregates to virions during their maturation. Consistent with our results, previous studies based on mass spectrometry approaches have demonstrated the presence of at least 70 host cellular and 71 HCMV proteins in mature virions (55,56). More recently, it has been demonstrated that HCMV may include both TGN and endosomal markers when undergoing final envelopment (32).…”
Section: Discussionsupporting
confidence: 92%
“…This finding leans toward excluding the possibility that IFI16 nonspecifically aggregates to virions during their maturation. Consistent with our results, previous studies based on mass spectrometry approaches have demonstrated the presence of at least 70 host cellular and 71 HCMV proteins in mature virions (55,56). More recently, it has been demonstrated that HCMV may include both TGN and endosomal markers when undergoing final envelopment (32).…”
Section: Discussionsupporting
confidence: 92%
“…The latter finding is in line with proteomic analyses of HCMV particles, in which peptides originating from pUL77 and pUL93 were detected (58,59). Also, capsid-association of pUL77 was previously seen after fractionation of extracellular HCMV particles into envelope, tegument, and capsid (28).…”
Section: Discussionsupporting
confidence: 83%
“…Its homologues, HSV-1 UL16, EBV BGLF2, and human cytomegalovirus (HCMV) UL94, are all present in the tegument layer of mature virions (24,(40)(41)(42)(43)(44), but the roles of the ORF33 homologues in herpesviral replication remain elusive. Although deletion of UL16 reduces the viral yield of HSV-1 (an alphaherpesvirus) only moderately (45), deletion of UL94 abolishes progeny virion production by HCMV (a betaherpesvirus) (46).…”
Section: Discussionmentioning
confidence: 99%